TEMPORAL AND SEASONAL VARIATION OF SEDIMENT MOVEMENT IN THE TERRACED PADDY FIELDS SYSTEM - SUKRISTIYONUBOWO, .; SETYORINI, D (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2010)
Temporal and seasonal variation of sediment movement in terraced paddy fields has been studied at Keji Village, in Semarang District for the Wet Season 2003-04 and the Dry Season 2004. Twelve terraced paddy fields with different number and size of terraces were used in this research,corresponding to four treatments and three replications. Terraces were flat, different in size, and descending to the river. The objective was to study the temporal and seasonal variations of sediment movement during rice growth in the wet season and the dry season. Measurements were conducted in the four treatments being tested including Farmer Practices, Farmer Practices + Rice Straw, Improved Technology, and Improved Technology + Rice Straw. Sampling and measuring of irrigation water discharge and suspended sediment were carried out at puddling, before planting, vegetative stage, and at generative stage. The highest temporal discharge as well as sediment concentration of irrigation water and suspended sediment both in wet and dry seasons were observed at the puddling stage and significantly different with the following rice growth stages. In contrast, the lowest temporal discharge and sediment concentration were found at the vegetative stage. Seasonal discharge and sediment concentration of irrigation water and suspended sediment in wet season were higher than in dry season. The highest incoming and outgoing sediments both in wet and dry season were observed at the vegetative stage and significantly different at generative stage, planting and puddling. The amount of seasonal incoming sediment were 4,422 ± 361 and 1,779 ± 126 kg ha-1 and the outgoing sediment were 3,345 ± 258 and 1,400 ± 113 kg ha-1 for the wet season 2003-04 and dry season 2004, respectively. The surplus of incoming sediment by outgoing sediment demonstrates the environmental services provided by terraced paddy fields system.